2002
DOI: 10.1128/jcm.40.9.3416-3420.2002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lysis Filtration and an Automated Blood Culture System (BACTEC) for Detection, Quantification, and Identification of Odontogenic Bacteremia in Children

Abstract: Lysis filtration (LyF) was compared with BACTEC PAEDS PLUS in estimating the prevalence of, and sensitivity for, detection of odontogenic bacteremia. Both real bacteremia and simulated bacteremia (seeded blood or saline samples) were assessed to determine the validity of LyF in estimating bacteremia. The simulated bacteremia was also used to assess the reliability of LyF to estimate intensity of bacteremia in CFU per milliliter of blood. Reference organisms were used to assess the abilities of LyF and BACTEC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…This system detects organisms by the fluorometric detection of CO 2 produced by growing organisms. It is known that this system can detect odontogenic bacteremia in 30 to 45 hours 36 . Additionally, we have ascertained that culture bottles inoculated with P. gingivalis of several concentrations (10, 100, 1000, and 10000 CFU/ml) signaled positive within 6 days in the preliminary experiment.…”
Section: Methodsmentioning
confidence: 78%
“…This system detects organisms by the fluorometric detection of CO 2 produced by growing organisms. It is known that this system can detect odontogenic bacteremia in 30 to 45 hours 36 . Additionally, we have ascertained that culture bottles inoculated with P. gingivalis of several concentrations (10, 100, 1000, and 10000 CFU/ml) signaled positive within 6 days in the preliminary experiment.…”
Section: Methodsmentioning
confidence: 78%
“…7 15 The results in this study are similar to those of a detailed study comparing the validity of BACTEC with that of lysis filtration in the detection of dental bacteraemia. 15 For these reasons, the data from the lysis filtration were used to assess the duration of bacteraemia. This was clearly highest during and up to 7.5 min and then diminished rapidly as most of the bacteraemia had been removed by the immune defence systems within 15 min (table 2).…”
Section: Discussionmentioning
confidence: 99%
“…A further 6 ml was processed by lysis filtration. 15 The remaining 1 ml was frozen and stored for future polymerase chain reaction analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies in our laboratory, we have shown that the Bactec 9240 culture and continuous monitoring system is effective in detecting oral bacteraemia, including Gram negatives and fastidious oral organisms, caused by periodontal probing (Daly et al 1997, 2001). The same Bactec system has also been shown to be effective in detecting these types of micro‐organisms in oral bacteraemias caused by a range of procedures (Lucas et al 2002, Tomas et al 2004, Kinane et al 2005). Studies on Bactec continuous monitoring systems have shown that 5 days are sufficient in routine circumstances to recover 97–99% of isolates (Wilson et al 1993, Doern et al 1997, Cockerill et al 2004).…”
Section: Discussionmentioning
confidence: 99%